Cold molecular outflows in the local Universe and their feedback effect on galaxies. Issue 4 (19th December 2018) - Fluetsch, A; Maiolino, R; Carniani, S; Marconi, A; Cicone, C; Bourne, M A; Costa, T; Fabian, A C; Ishibashi, W; Venturi, G
ABSTRACT: We study molecular outflows in a sample of 45 local galaxies, both star forming and active galactic nucleus (AGN), primarily by using CO data from the Atacama Large Millimeter/submillimeter Array (ALMA) archive and from the literature. For a subsample, we also compare the molecular outflow with the ionized and neutral atomic phases. We infer an empirical analytical function relating the outflow rate simultaneously to the star formation rate (SFR), L AGN, and galaxy stellar mass; this relation is much tighter than the relations with the individual quantities. The outflow kinetic power shows a larger scatter than in previous, more biased studies, spanning from 0.1 to 5 per cent of L AGN, while the momentum rate ranges from 1 to 30 times L AGN / c, indicating that these outflows can be both energy driven, but with a broad range of coupling efficiencies with the interstellar medium (ISM), and radiation pressure driven. For about 10 per cent of the objects, the outflow energetics significantly exceed the maximum theoretical values; we interpret these as 'fossil outflows' resulting from activity of a past strong AGN, which has now faded. We estimate that, in the stellar mass range probed here ($\gt 10^{10}\, {\rm M}_{\odot }$ ), less than 5 per cent of the outflowing gas escapes the galaxy. The molecular gas depletion time associated with the outflow can be as short as a few million years in powerful AGN; however, the total gas (H2  + H i ) depletion times are much longer. Altogether, our findings suggest that even AGN-driven outflows might be relatively ineffective in clearing galaxies of their entire gas content, although they are likely capable of clearing and quenching the central region.